Victimological Prevention of Crime against Life and Health - MUSSAYEV, Daniyarbek (Journal of Advanced Research in Law and Economics; Vol 8 No 5 (2017): JARLE Volume VIII Issue 5(27) Fall 2017, 2018)
The article focuses on the peculiarities of victimological prevention of criminal offense against human life and health. This kind of offense is one of the most studied objects of criminology. However, a number of issues related to prevention of crime against life and health remain unsolved. This circumstance makes the aggrieved person's victimity an especially important object of preventive measures and raises interest in the research of victimological crime prevention. This work focuses on the search for ways to improve the preventive measures system for crime against life and health. The article considers the notion and matter of victimological prevention based on victimological research, and also emphasizes the importance of such research in crime prevention. It provides the peculiarities of victimological prevention objects – aggrieved and potential victims who have suffered a criminal offense against their life and health, as well as provides their types and classification. A broad overview of the international experience in protecting victims of violent crime is presented. The article analyzes victimological research and victimological prevention systems in other countries. It also describes the main trends in protecting crime victims used within victimological prevention in Western countries. The author presents his view of the importance of studying the best victim protection practices from other countries. It is suggested to develop a victimological propaganda program for the population, which is one of the most preferable trends in the improvement of victimological prevention of crime against life and health. The article provides a comprehensive description of its fulfillment taking into account the customs and traditions of the Republic of Kazakhstan